Tides and the flow of Rutford Ice Stream, West Antarctica - Gudmundsson, Hilmar (Journal of Geophysical Research, 2007)
[1] Surface speeds of Rutford Ice Stream, West Antarctica, are known to vary by around 10–20% (depending on location) with a fortnightly periodicity corresponding to a spring‐neap tidal cycle. The reasons for these periodic variations in flow are unclear. Here the possible role of tidal stress transmission upstream of the grounding line in affecting rates of basal motion is investigated. It is found that nonlinear rheological effects within the till, when coupled with transmission of tidal stresses within the ice that are linearly related to tidal amplitude, can give rise to the type of periodic oscillations in flow observed. This nonlinear interaction between tidal forcing and till deformation increases the mean ice flux across the grounding line by a few percent above what might be expected in the absence of tidal forcing. Periodic velocity fluctuations of this type have not been observed on other ice streams. However, modeling suggests that this may be due to lack of data and that such flow variations are likely to be common features of active ice streams draining into the Ronne Ice Shelf, as well as of other ice streams subjected to similar tidal forcing.